BUDAYA SIRI’ DAN BESARAN UANG PANAI’ DALAM PERNIKAHAN MASYARAKAT BUGIS - Muhammad Rafli; Syukur, Muhammad (DISCOURSE: Indonesian Journal of Social Studies and Education, 2024)
This research aims to investigate the relationship between siri' culture and the amount of panai' money in the context of Bugis community marriage. By adopting a subjective approach that emphasizes in-depth and interpretive examination, this research seeks to gain a comprehensive understanding of siri' cultural practices and their influence on determining the amount of panai' money. The focus of this research is PaoPao Village, Tanete Rilau District, which is the subject of research with several individuals interviewed using a structured interview guide. Apart from that, participatory observation was also carried out to observe interactions between Bugis tribal communities in the process of determining panai money. The collected data was then analyzed qualitatively using the thematic analysis method on interview transcripts and observation notes. Research findings show that siri' cultural practices have a significant impact on determining the amount of panai' money in Bugis weddings, influencing perceptions, values ​​and attitudes regarding responsibility and commitment in marital relationships. The results of the analysis also reveal the importance of maintaining the continuity and relevance of the siri' and Uang Panai' cultural traditions amidst the social and cultural changes occurring in Bugis society. Triangulation of data from interviews and participant observation also strengthens the validity of this research's findings. Thus, this research makes an important contribution to the understanding of cultural dynamics and traditions in the marriage context of the Bugis community, as well as providing a basis for the development of relevant cultural policies and interventions.